Sero Prevalence of HIV in Pakistan: A study performed in Jail Prisoners. - Nordin, Simbak; Shamim Ahmed, Khan; Atif, Amin Baig (CreateSpace Independent Publishing Platform, 2014)
HIV/AIDS is the most important modifiable cause of premature death. Preventing HIV/AIDS is the single most effective thing that PLWHA can do to enhance the quality and length of their lives. The purpose of this study was to use an established theoretical framework to examine and describe the Prevalence of HIV/AIDS among Jail-inmates of Distt: Malir Jail, Karachi Sindh Pakistan. A cross-sectional survey (n = 427) Tests was conducted among prisoners to identify the HIV that influence the immune system of the body and after several years other systems are effected. The survey was also conducted to determine the association of STI with HIV among study population, their access of condom and strategies and provision of other preventing, medical, psychological support. The results showed that: (1) the current prevalence of HIV/AIDS rate among Jail-inmates of Distt: Malir Jail is (10) 2 % Most of Population found HIV Positive are Injecting drug users ; (2) Sixteen percent ( 16%) can access the condom (3) Fifty five percent (55%) gave the history of STIs ( Gonorrhoea ) Pakistani Prisons health care system still has a long distance to travel down the path of Knowledge of Transmission & prevention of on STIs -initiated practice. The identification of High risk to low risk population and provision of preventive services among inmates is a viable framework on which to base interventions designed to promote HIV prevention in the jails of Pakistan & it practice by preventive care . Understanding the role of attitudes and perceived behavioural control is of central importance to ensure all potential primary care physicians can promote the chain of prevention expeditiously whenever the need arises.